PERLINDUNGAN HUKUM ATAS PEMUTUSAN RELASI KERJA DALAM GIG ECONOMY MENURUT TEORI PHILIPUS M. HADJON: LEGAL PROTECTION FOR TERMINATION OF EMPLOYMENT RELATIONS IN THE GIG ECONOMY ACCORDING TO PHILIPUS M. HADJON THEORY - Mohamad Dino Setiawan; A. Basuki Babussalam (Journal Presumption of Law, 2026)
The The development of the gig economy has brought significant changes to employment patterns, which are increasingly flexible, task-based, and not always tied to conventional employment relationships. On the one hand, this flexibility provides economic opportunities; on the other hand, it raises legal issues, particularly regarding the vulnerability of gig workers to unilateral termination without adequate protection mechanisms. This situation indicates an imbalance in bargaining power between employers and gig workers, as reflected in termination practices that place workers in a vulnerable position when employment is terminated unilaterally. This study aims to analyze the forms of legal protection against termination in the gig economy from the perspective of Philipus M. Hadjon's Legal Protection Theory. The research method employed is normative legal research using statutory and conceptual approaches. The results show that legal protection for gig workers in cases of termination has not been comprehensively regulated within the Indonesian labor law system. Existing protection tends to be repressive, meaning it is only available after disputes arise, while preventive protection remains inadequate. Therefore, it is necessary to strengthen regulations to provide legal certainty and justice for gig workers facing the risk of termination.